2021
DOI: 10.3390/nano11030751
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun PCL-Based Vascular Grafts: In Vitro Tests

Abstract: Background: Electrospun fibers have attracted a lot of attention from researchers due to their several characteristics, such as a very thin diameter, three-dimensional topography, large surface area, flexible surface, good mechanical characteristics, suitable for widespread applications. Indeed, electro-spinning offers many benefits, such as great surface-to-volume ratio, adjustable porosity, and the ability of imitating the tissue extra-cellular matrix. Methods: we processed Poly ε-caprolactone (PCL) via elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…While we did not look at crystallinity effects, based on our SEM analysis we can confirm no adverse effects on fibre roughness. Interestingly, this approach of varying multiple parameters to achieve a range of fibre sizes has been commonly done in the literature [ 11 , 38 , 39 ]. One notable study showed that the best results were achieved using a multi-parameter approach to achieve a range of fibre sizes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…While we did not look at crystallinity effects, based on our SEM analysis we can confirm no adverse effects on fibre roughness. Interestingly, this approach of varying multiple parameters to achieve a range of fibre sizes has been commonly done in the literature [ 11 , 38 , 39 ]. One notable study showed that the best results were achieved using a multi-parameter approach to achieve a range of fibre sizes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fiber diameter and the degree of orientation were determined based on ten SEM (S-3400 N, Hitachi High-Tech Analytical Science Ltd., Tubney Woods, Abington, UK) images: five for each of the two relative collector velocities. Afterwards, the images were analyzed using image analysis software (AxioVision ® , Carl Zeiss AG, Jena, Germany) as described by Fricke et al (2019) [ 14 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…PCL is a linear, hydrophobic, aliphatic polyester with high mechanical strength and is biocompatible as well as biodegradable [ 172 , 173 ]. Chemotherapeutics [ 154 , 157 , 159 , 174 , 175 , 176 , 177 , 178 , 179 ], antimicrobials [ 162 , 180 , 181 ], and anti-inflammatory drugs [ 160 , 182 ] have been delivered using PCL.…”
Section: Synthetic Biopolymer Scaffolds For Therapeutic Ev Deliverymentioning
confidence: 99%